2002
DOI: 10.1258/135581902320432723
|View full text |Cite
|
Sign up to set email alerts
|

How much variation in clinical activity is there between general practitioners? A multi-level analysis of decision-making in primary care

Abstract: The amount of variability in clinical activity that can definitively be linked to the practitioner in primary care is similar to that recorded in studies of the secondary sector. With primary care doctors increasingly being grouped into larger professional organisations, we can expect application of multi-level techniques to the analysis of clinical activity in primary care at different levels of organisational complexity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 19 publications
5
54
0
Order By: Relevance
“…A number of studies adopted a multilevel approach as a statistical solution, assuming the frequency of services as a dependent variable (encounters, referrals, or prescriptions). In one study the variance unexplained by the models at the practice level was between 12.9% and 27.2% according to the type of service [41]. Two more studies demonstrated a much lower residual unexplained variance at the practice level, comparable to the one found in the present study (0.1% for prescription number [42] and 3.6% for referrals [43]).…”
Section: Resultssupporting
confidence: 66%
“…A number of studies adopted a multilevel approach as a statistical solution, assuming the frequency of services as a dependent variable (encounters, referrals, or prescriptions). In one study the variance unexplained by the models at the practice level was between 12.9% and 27.2% according to the type of service [41]. Two more studies demonstrated a much lower residual unexplained variance at the practice level, comparable to the one found in the present study (0.1% for prescription number [42] and 3.6% for referrals [43]).…”
Section: Resultssupporting
confidence: 66%
“…Female physicians showed better blood pressure registrations, as did physicians with Ͻ10 years of work experience. Previous studies (11,15) have also shown a positive relation between female physicians and quality-of-care aspects. Regarding the choice of treatment, we could not identify specific general practitioner characteristics that were related to better treatment, but the deviance test showed that there remained significant differences between general practitioners after controlling for the effect of the included physician, practice, and patient characteristics.…”
Section: Factors Influencing Blood Pressure Carementioning
confidence: 67%
“…Assessing the relative influence of specific physician and practice characteristics in relation to patient factors is important for the development of targeted interventions to improve the quality of care (15). Our study showed that several patient-related factors are associated with the quality of hypertension management.…”
Section: Factors Influencing Blood Pressure Carementioning
confidence: 76%
See 1 more Smart Citation
“…Other factors can, however, contribute to these variations, such as characteristics of the patients, socioeconomic aspects, cultural or leadership issues, among others 28,29 . In this study, for instance, vaginal delivery is significantly protects from the use of inhaled oxygen,; the same goes for births in the Northern and Northeastern regions.…”
Section: Discussionmentioning
confidence: 99%